The Structure of the Mitochondrial Membrane: Inferences from Permeability Properties - Tedeschi, Henry (The Rockefeller University Press, 1959)
Mitochondria possess a semipermeable membrane with properties similar to the cell membrane. Despite the presence of a limiting membrane, mitochondria swell approximately 4 to 5 times their original volume without lysis or loss of internal solute. For this reason, it has been argued that the membrane might be convoluted. The present kinetic study of the permeability of isolated mitochondria was undertaken to clarify this question. A photometric method described previously was used. In the case of highly lipid soluble penetrants, the results suggest that neither the permeability nor the surface area available for penetration varies significantly during considerable swelling. These results may be interpreted to mean that the mitochondrial membrane is convoluted. For highly polar compounds, the permeability of the membrane also remains unchanged during swelling, but the surface area available to penetration increases. These results may be interpreted to mean that in this latter case, the surface of the convolutions becomes available only after they are unfolded by swelling. The simplest model that can explain the permeability properties of this membrane consists of a bimolecular lipid layer where the inner monomolecular layer is convoluted.